Internalization of microparticles by platelets is partially mediated by toll-like receptor 4 and enhances platelet thrombogenicity. (February 2020) - Jerez-Dolz, Didac; Torramade-Moix, Sergi; Palomo, Marta; Moreno-Castaño, Ana; Lopez-Vilchez, Irene; Hernandez, Rosa; Badimon, Juan Jose; Zafar, M. Urooj; Diaz-Ricart, Maribel; Escolar, Gines
Abstract: Background and aims: Circulating platelet microparticles (PMP) are the most abundant in bloodstream, are highly procoagulant and contribute to cross-talk with inflammatory cells. The aim of the present study was to investigate the interactions of PMP with platelets and explore the involvement of toll-like receptor 4 (TLR-4). Methods: PMP were separated by ultracentrifugation of expired platelet concentrates and added to: i) washed platelets, to confirm uptake, by flow cytometry and confocal and transmission electron microscopy, ii) platelet rich plasma (PRP), to assess changes in platelet function due to uptake by aggregometry in response to ADP; and iii) whole blood, to evaluate heterotypic aggregate (HA) formation by flow cytometry. Moreover, whole blood previously enriched with platelets with internalized PMP was used to explore modifications in thromboelastometry parameters (ROTEM). The inhibitory action of anti-TLR-4 was investigated. Results: Confocal and ultrastructural microscopy studies revealed PMP internalization by platelets. Flow cytometry showed PMP-platelet association ( p  < 0.01 vs controls, at different PMP dilutions). PMP, at 1/20 dilution, increased HA ( p  < 0.05 vs controls), the percentage of maximal platelet aggregation to ADP ( p  < 0.05 vs controls), and accelerated clotting and clot formation times ( p  < 0.05 vs controls). Incubation of platelets with anti-TLR-4 prior to exposure to PMP reduced PMP-platelet association ( p  < 0.05 vs absence of the antibody), prevented HA formation, reduced maximal platelet aggregation and normalized ROTEM parameters. Conclusions: Platelets exhibit internalization ability towards their own PMP, a process that potentiates their thrombogenicity and is partially mediated by the innate immunity receptor TLR-4. Graphical abstract: Image 1 Highlights: Microparticles from platelet origin are the most abundant vesicles in bloodstream. Platelets have Toll Like Receptors (TLR) with key role in inflammation and immunity. Platelets internalize microparticles of platelet origin (PMP). PMP internalization by platelets is mediated by innate immune receptor TLR4. Our findings reveal that platelet uptake of PMP enhances their thrombogenicity.